Efficacy of a text messaging (SMS) based smoking cessation intervention for adolescents and young adults: Study protocol of a cluster randomised controlled trial - Haug Severin; Meyer Christian; Dymalski Andrea; Lippke Sonia; John Ulrich (BMC, 2012)
Abstract Background Particularly in groups of adolescents with lower educational level the smoking prevalence is still high and constitutes a serious public health problem. There is limited evidence of effective smoking cessation interventions in this group. Individualised text messaging (SMS) based interventions are promising to support smoking cessation and could be provided to adolescents irrespective of their motivation to quit. The aim of the current paper is to outline the study protocol of a trial testing the efficacy of an SMS based intervention for smoking cessation in apprentices. Methods/Design A two-arm cluster-randomised controlled trial will be conducted to test the efficacy of an SMS intervention for smoking cessation in adolescents and young adults compared to an assessment only control group. A total of 910 daily or occasional (≥ 4 cigarettes in the preceding month and ≥ 1 cigarette in the preceding week) smoking apprentices will be proactively recruited in vocational school classes and, using school class as a randomisation unit, randomly assigned to an intervention group (n = 455) receiving the SMS based intervention or an assessment only control group (n = 455). Individualised text messages taking into account demographic data and the individuals' smoking behaviours will be sent to the participants of the intervention group over a period of 3 months. Participants will receive two text messages promoting smoking cessation per week. Program participants who intend to quit smoking have the opportunity to use a more intensive SMS program to prepare for their quit day and to prevent a subsequent relapse. The primary outcome measure will be the proportion of participants with 7-day point prevalence smoking abstinence assessed at 6-months follow-up. The research assistants conducting the baseline and the follow-up assessments will be blinded regarding group assignment. Discussion It is expected that the program offers an effective and inexpensive way to promote smoking cessation among adolescents and young adults including those with lower educational level and independent of their motivation to quit. Trial registration number ISRCTN: ISRCTN19739792